PENOKOHAN, ALUR, LATAR, TEMA, DAN AMANAT, SERTA NILAI MORAL DALAM NOVEL SURGA RETAK KARYA SYAHMEDI DEAN - Ana, Helena; Rustiati, Rustiati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Katolik Widya Mandala Madiun, 2015)
This research purposes to know and explains the characterization, plot, setting, theme, and messages and moral value in the novel entitled Surga Retak written by Syahmedi Dean. This research uses descriptive qualitative approach, it means the data which is used to support this research is in the form of sentence and paragraph. The finding of the research: (1) The techniques which is used by the author to describe the character are expository technique, dramatic technique, and mixture technique. The main character is Suri, while the minor characters are Murad, Fatma, Koh Liang, Aminah, Amrul, Anto, Tante Nur, Nek Gintuk, Wilson, and Esther Ang. (2) The plot which is used is progressive plot because the story begins by the appearance of the conflict, and continues by the raising of the conflict, then the resolution, and finally reorientation. (3) The setting of places are Indonesia more details in Medan, rantau makmur village, barabatu, rubber botanical, and in Singapore. The setting of time is about 1983, in the era of President Soeharto, and his vice Umar wirahadikusumah. The social setting is in the lower class society. (4) The major theme is struggling. The minor themes are murdering, gambling, and human trafficking. (5) The message which is delivered to the reader is positive value.